2008
DOI: 10.1182/blood-2008-01-133801
|View full text |Cite
|
Sign up to set email alerts
|

Differences in lymphocyte developmental potential between human embryonic stem cell and umbilical cord blood–derived hematopoietic progenitor cells

Abstract: Hematopoietic progenitor cells derived from human embryonic stem cells (hESCs) develop into diverse mature hematopoietic lineages, including lymphocytes. Whereas functional natural killer (NK) cells can be efficiently generated in vitro from hESC-derived CD34 ؉ cells, studies of T-and B-cell development from hESCs have been much more limited. Here, we demonstrate that despite expressing functional Notch-1, CD34 ؉ cells from hESCs did not derive T cells when cocultured with OP9 cells expressing Delta-like 1, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 63 publications
4
60
0
4
Order By: Relevance
“…A report of anterior foregut endoderm derived from human ES and IPS cells holds more promise for robust and controlled generation of TECs, although that goal has not yet been reached . By contrast, substantial progress has been reported in generating T cells from both human and mouse hematopoietic stem cells or from ES cells in vitro (Schmitt et al, 2004;de Pooter and Zuniga-Pflucker, 2007;Awong et al, 2008;Martin et al, 2008) using an OP9 cell line expressing delta-like 1 (OP9-DL1) that can sustain most aspects of T cell differentiation in vitro (Schmitt and Zuniga-Pflucker, 2002;Holmes and ZunigaPflucker, 2009). So, why make TECs at all?…”
Section: Reviewmentioning
confidence: 99%
“…A report of anterior foregut endoderm derived from human ES and IPS cells holds more promise for robust and controlled generation of TECs, although that goal has not yet been reached . By contrast, substantial progress has been reported in generating T cells from both human and mouse hematopoietic stem cells or from ES cells in vitro (Schmitt et al, 2004;de Pooter and Zuniga-Pflucker, 2007;Awong et al, 2008;Martin et al, 2008) using an OP9 cell line expressing delta-like 1 (OP9-DL1) that can sustain most aspects of T cell differentiation in vitro (Schmitt and Zuniga-Pflucker, 2002;Holmes and ZunigaPflucker, 2009). So, why make TECs at all?…”
Section: Reviewmentioning
confidence: 99%
“…Although T precursor activity was not addressed, these data suggest that the CD34 ϩ CD43 ϩ population may contain multipotent HPC. However, a recent report from Martin et al (7) indicated that such hESC-derived HPC lack T lineage potential. hESC-derived CD34 ϩ cells, introduced in fetal thymic organ cultures or in cocultures with Delta-like 1 expressing OP9 stromal cells (OP9-DL1), did not generate T cells, in contrast to cord blood-derived CD34 ϩ cells.…”
mentioning
confidence: 99%
“…To allow more access to developing cells and improving conditions that support or inhibit development of T cells, a Notch ligand-expressing OP9-DL1 stromal cells have been used to derive T cells from multiple progenitor cell populations expressing CD34 and CD45 such as human BM, umbilical cord blood, and mouse ESCs (RF. de Pooter , et al 2003;CH. Martin, et al, 2008;TM.…”
Section: T-and B-lymphocytesmentioning
confidence: 99%